2020
DOI: 10.1016/j.joen.2020.06.037
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Perspectives of Pulp Regeneration

Abstract: Introduction: A sound and vital pulp is an essential prerequisite for long-term tooth survival and preservation. However, current endodontic treatment concepts are based on the removal of inflamed or necrotic pulp tissue and the replacement by a synthetic biomaterial. Recently, total or partial pulp regeneration has been proposed as an alternative treatment concept. The aim of this review was to evaluate the current options of pulp treatment and regenerative approaches, both for immature and mature teeth, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 107 publications
(159 reference statements)
0
58
0
1
Order By: Relevance
“…In this study, 20 mL of 1.0% NaClO will be used for irrigation with a side-vented needle and an ultrasonic irrigation device to minimise the possibility of extrusion of irrigates into the periapical space and to enhance the disinfection efficacy of NaClO. Following the recommendation from the AAE, NaClO should be flushed away from the root canal with saline to reduce any lingering toxicity [ 4 , 60 ]. EDTA irrigation will also be applied in this study, as EDTA has been demonstrated to promote the survival of stem cells [ 61 ], stimulate the release of growth factors embedded in the dentin matrix, and enhance the odontogenic differentiation of migrated cells and angiogenesis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, 20 mL of 1.0% NaClO will be used for irrigation with a side-vented needle and an ultrasonic irrigation device to minimise the possibility of extrusion of irrigates into the periapical space and to enhance the disinfection efficacy of NaClO. Following the recommendation from the AAE, NaClO should be flushed away from the root canal with saline to reduce any lingering toxicity [ 4 , 60 ]. EDTA irrigation will also be applied in this study, as EDTA has been demonstrated to promote the survival of stem cells [ 61 ], stimulate the release of growth factors embedded in the dentin matrix, and enhance the odontogenic differentiation of migrated cells and angiogenesis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, root canal therapy (RCT) is the most acceptable treatment for pulp necrosis, based on the replacement of inflamed or necrotic pulp tissue with artificial filling materials [ 4 ]. However, this conventional therapy does not restore the vitality of damaged pulp or reconstitute the neurovascular system [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the present case report the avulsed and reimplanted immature permanent tooth underwent apexification, revitalization of necrotic open apex teeth might be considered a valid alternative treatment to the apical plug with MTA [ 2 ]. Regeneration procedures have been recently proposed also in mature permanent teeth [ 20 ], but they should be further confirmed in case of avulsion and reimplantation. In addition, a regenerative endodontic approach has been very recently suggested as a treatment strategy to arrest progressive development of root resorption of young permanent teeth, with the aim to promote new periodontal ligament attachment to ankylosed teeth [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of permanent immature teeth may be halted owing to various harmful stimuli such as caries, trauma, anatomic variations which leads to thin and fragile dentinal walls. The long-term survival of these teeth is conceded due to open apices, large apical diameters and short roots 1,2 . Conventional techniques of root canal filling rely on the presence of an apical constriction at the apex of the tooth.…”
Section: Introductionmentioning
confidence: 99%